When the vision of Islamic boarding school decreases: education and scarcity of Ulemas - Afrizal M; Jamaluddin; Agus Firdaus Chandra; Jumni Nelli; Alaiddin Koto; Muhammad Hanif (Technium Social Sciences Journal, 2023)
The decrease in the vision of islamic boarding school has indirectly led to a scarcity of ulemas. The learning process which leads students to insights about ulemas is no longer achieved. This study aims to analyze the effect of changes in the vision of Islamic boarding school on the scarcity of ulemas. A total of 30 students were randomly selected in this study. The data were collected by interview. The participants were asked about their interest in becoming ulemas. Most of the participants answered that they were not interested in becoming ulemas, less than half said they were not interested and a few were unsure. The results of the study show that reducing the vision of the islamic boarding school has the potential to increase the scarcity of ulemas. This study is limited to students and has not involved teachers and institutions. It is expected that there will be a study that summarizes these three factors so that the results obtained are more comprehensive